Loss of Akap1 Exacerbates Pressure Overload-Induced Cardiac Hypertrophy and Heart Failure - Schiattarella, Gabriele G.; Boccella, Nicola; Paolillo, Roberta; Cattaneo, Fabio; Trimarco, Valentina; Franzone, Anna; D’Apice, Stefania; Giugliano, Giuseppe; Rinaldi, Laura; Borzacchiello, Domenica; Gentile, Alessandra; Lombardi, Assunta; et al. (Frontiers in Physiology, 2018)
Left ventricular hypertrophy (LVH) is a major contributor to the development of heart failure (HF). Alterations in cyclic adenosine monophosphate (cAMP)-dependent signaling pathways participate in cardiomyocyte hypertrophy and mitochondrial dysfunction occurring in LVH and HF. cAMP signals are received and integrated by a family of cAMP-dependent Protein Kinase A (PKA) anchor proteins (AKAPs), tethering PKA to discrete cellular locations. AKAPs encoded by the Akap1 gene (mitoAKAPs), promote PKA mitochondrial targeting, regulating mitochondrial structure and function, reactive oxygen species production and cell survival. To determine the role of mitoAKAPs in LVH development, in the present investigation, mice with global genetic deletion of Akap1 (Akap1-/-), Akap1 heterozygous (Akap1+/-) and their wild-type (wt) littermates underwent transverse aortic constriction (TAC) or the SHAM procedure for one week. In wt mice, pressure overload induced downregulation of AKAP121, the major cardiac mitoAKAP. Compared to wt, Akap1-/- mice did not display basal alterations in cardiac structure or function, cardiomyocyte size or fibrosis. However, loss of Akap1 exacerbated LVH and cardiomyocyte hypertrophy induced by pressure overload, and accelerated the progression towards HF in TAC mice, and these changes were not observed upon prevention of AKAP121 degradation in Seven In-Absentia Homolog 2 (Siah2) knockout mice (Siah2-/-). Loss of Akap1 was also associated to a significant increase in cardiac apoptosis as well as lack of activation of Akt signaling after pressure overload. Taken together, these results demonstrate that in vivo genetic deletion of Akap1 enhances LVH development and accelerates pressure overload-induced cardiac dysfunction, pointing at Akap1 as a novel repressor of pathological LVH. These results confirm and extend the important role of mitoAKAPs in cardiac response to stress.